THE EFFECT OF E-LEARNING ON THE ACQUISITION OF READING IN READING AND TEXTS, AND THE DEVELOPMENT OF CREATIVE READING SKILLS AND INNOVATIVE THINKING CONCEPTS FOR LITERARY FIFTH STUDENTS - Dr. KHAMAEL SHAKIR GHANIM, M. Mohammed Majid Taha Shihab, Dr.Falah Salih Hussen (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to show the impact of e-learning on the acquisition of literacy concepts among literary fifth yearstudents in reading and texts. It also aims to develop their innovative reading and thinking skills. The study sample is the schools of Salah al-Din Governorate. Three schools were randomly selected, one in each district of the governorate center. The researchers prepared 25 items in the multiple-choice formula. These items were authenticand consistent.Following the T-test of one sample and two independent samples, and the mono- analysis of variance in treating the data statistically, this study in its limits came up withthe following two results: -There was no statistically significant difference at the level of (0.05) in creative reading skill among students of the three schools. - No statistically significant difference at a significant level (0.05) among the students of the three schools according to the gender variableare reported.